Graduate education in public administration: the introductory course - Schachter Hindy Lauer
There are four sections in this article. The first describes the methodology for learning about introductory MPA courses. The recond indentifies the major topics covered. The third analyses the most frequently used books. The four the offers conclusions. This article analyses the content of MPA programs' introductory course and the implecations of such context for normative debates on MPA education. Among the topics explored are the role of "classic" works in the introductory focus. Further this examines the topic and types of readings MPA programs' introductory courses contain. Such examination offers a picture of the skills and information faculty consider foundational to MPA study; it identifies the areas pr
Keywords: Master of Public Administration(MPA); Graduate Education; Public Administration -- Study and Teaching